The Candymakers : The Candymakers #1 - Mass, Wendy, 1967- (New York : Little, Brown, 2010)
When four twelve-year-olds, including Logan, who has grown up never leaving his parents' Life Is Sweet candy factory, compete in the Confectionary Association's annual contest, they unexpectedly become friends and uncover secrets about themselves during the process.
Keywords: Candy -- Fiction; Secrets -- Fiction; Contests -- Fiction; Friendship -- Fiction; Candy -- Fiction; Secrecy -- Fiction; Contests -- Fiction; Friendship -- Fiction